Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1042/bsr20210344
|View full text |Cite
|
Sign up to set email alerts
|

Serum biomarker discovery related to pathogenesis in acute coronary syndrome by proteomic approach

Abstract: Acute coronary syndrome (ACS) results from inadequate supply of blood flow from the coronary arteries to the heart or ischemia. ACS has an extremely high morbidity and mortality. The levels of biomarkers currently used for detection of ACS also increase in response to myocardial necrosis and other diseases and are not elevated immediately after symptoms appear, thus limiting their diagnostic capacity. Therefore, we aimed to discover new ACS diagnostic biomarkers with high sensitivity and specificity that are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Several bioinformatic analyses have shown that LRG1 may serve as a useful biomarker in cardiovascular diseases ( 20 23 ). For instance, one study demonstrated that LRG1 is elevated in patients with acute coronary syndrome compared with healthy controls ( 20 ). Another proteomic analysis revealed that LRG1 may be a potential biomarker for early diagnosis of heart failure ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several bioinformatic analyses have shown that LRG1 may serve as a useful biomarker in cardiovascular diseases ( 20 23 ). For instance, one study demonstrated that LRG1 is elevated in patients with acute coronary syndrome compared with healthy controls ( 20 ). Another proteomic analysis revealed that LRG1 may be a potential biomarker for early diagnosis of heart failure ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, plasma LRG1 was elevated from admission to D1, and then gradually decreased until D30 in patients with STEMI. The possible explanations might be as follows: (1) LRG1, as a vasculopathy factor, is positively associated with abnormal angiogenesis and acute inflammation; meanwhile, the latter factors are enhanced in patients with STEMI ( 11 , 20 ). Hence, plasma LRG1 was increased in patients with STEMI compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass spectrometry‐based methods have been used to identify novel plasma biomarkers of acute atherothrombosis using a two‐step approach of unbiased proteomic discovery analysis in a smaller sample set, followed by targeted validation of selected markers in a larger sample set. Shin et al used LC‐MS/MS in a discovery proteomics analysis of plasma from 50 patients with acute coronary syndrome (ACS) and 50 controls, followed by validation in 120 ACS and 120 controls by targeted MS proteomics for absolute quantification of seven identified top candidates, 96 replicating four (AGP1, C5, LRG1, vitronectin) as significantly increased and one (gelsolin) as decreased in ACS. All four upregulated proteins are expressed predominantly in liver, not myocardium, and thus possibly linked to the pathogenic mechanisms in the acute arterial thrombotic event, rather than reflecting cardiomyocyte injury.…”
Section: Plasma Proteomics In Atherothrombosismentioning
confidence: 99%
“…1 Clinical categorization of ACS includes unstable angina pectoris (uAP), ST-segment elevation myocardial infarction (STEMI) and Non-STEMI (NSTEMI). 2 While uAP was traditionally defined as ACS without an elevation in cardiac enzymes, 3 this view has been changed since the introduction of novel high-sensitivity cardiac troponin assay (hs-cTnT) assays. 4 The hs-assays can detect cTnT elevations at concentrations 10–100-fold lower compared to conventional assays, 5 resulting in improved acute myocardial infarction (AMI) detection and identification of smaller infarcts previously misdiagnosed as uAP.…”
Section: Introductionmentioning
confidence: 99%